A high-nickel cathode material co-doped with rare earth metals, alkaline earth metals, and halogens and its preparation method.
Through the co-doping technology of rare earth metals, alkaline earth metals and halogen elements, the problems of poor structural transformation and thermal stability of high-nickel cathode materials during the cycle process are solved, and the battery performance is improved and the cycle life is extended.
Patent Information
- Application Number
- CN202411054035.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-02
AI Technical Summary
High-nickel ternary cathode materials are prone to structural changes during the cycle, resulting in rapid attenuation of battery capacity and poor thermal stability, which affects the long-cycle stability and safety of the battery.
Using co-doping technology of rare earth metals, alkaline earth metals and halogen elements, a new composite with specific electronic structure is prepared through high-temperature solid phase treatment, which improves ion conductivity and electron stability, and generates fast ions on the surface of the material. Conductor cladding.
Improves the overall performance and thermal stability of the battery, extends the cycle life of the battery, and improves the rate performance of the material and the efficiency of the Coulomb.
Smart Images

Figure CN118572100B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals and halogen elements and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have quickly become the preferred power source for portable electronic devices due to their high energy density, long cycle life, and low self-discharge rate. As the global demand for renewable energy and electric vehicles grows, the market demand for lithium-ion batteries as power batteries continues to rise, and scientists and engineers are constantly exploring new materials and technologies to further improve the performance of lithium-ion batteries. As the core of power batteries, positive electrode materials directly affect battery energy density, cycle life, and safety, and are key to the development of the electric vehicle industry.
[0003] High-nickel ternary cathode materials are the key technical foundation and guarantee for lithium-ion power batteries to achieve high energy density and long battery life due to their high energy density and relatively low cost. A higher nickel content can not only significantly improve the energy density of the battery, but also reduce the use of cobalt, thereby reducing dependence on scarce resources. However, high-nickel materials face many challenges in practical applications, such as short cycle life and poor thermal stability. The root cause is that high-nickel materials are prone to structural transformation during the cycle, resulting in rapid battery capacity decay. High-nickel ternary cathode materials shrink / expand anisotropically during the charge and discharge process, which can easily cause intergranular cracks and particle breakage, seriously affecting the long-cycle stability of the battery. In addition, with the increase in nickel content, it also faces problems such as fast capacity decay and poor safety caused by poor structure and thermal stability, which seriously restricts the further application of high-nickel ternary cathode materials in lithium-ion power batteries. In order to improve the performance of lithium-ion batteries with high-nickel cathode materials, a large number of modification methods have been studied and applied.
[0004] As an effective modification method, element doping is widely used to regulate the structure and electrochemical properties of high-nickel layered oxide cathode materials. The spatial distribution of doping elements has a significant impact on the material structure and performance. The existing doping methods are mainly single element doping, however, the doping of a single element often has limited effect. 2+ Although alkaline earth metal ion doping can effectively inhibit the Li + / Ni 2+ Mixing can stabilize the structure, but it does not significantly improve the cycle performance of the positive electrode material under high pressure. - Anion doping, represented by , can significantly improve the high-voltage performance of positive electrode materials, while anion doping can cause Li + / Ni 2+The mixing is aggravated, resulting in unstable long-cycle performance. In addition, the uneven distribution of doping elements in the material may lead to inconsistent local electrochemical performance, affecting the overall performance of the battery. It is worth noting that doping elements may change the crystal structure of the material, making it more susceptible to phase change during the cycle, resulting in accelerated capacity decay. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the first object of the present invention is to provide a high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element; the second object of the present invention is to provide a preparation method of a high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element.
[0006] In order to achieve the first purpose, the technical solution adopted by the present invention is:
[0007] A high-nickel positive electrode material co-doped with a rare earth metal, an alkaline earth metal, and a halogen element, wherein the molecular formula of the high-nickel positive electrode material is as follows:
[0008] Li(Ni x Co y Mn 1-x-y ) 1-a-2 / 3b-1 / 3c P a Q b O 2-c L c ;
[0009] Wherein, P is a rare earth metal, Q is an alkaline earth metal, and L is a halogen element;
[0010] Among them, x≥0.6, 0.01≤a≤0.02, 0.01≤b≤0.02, 0.01≤c≤0.02.
[0011] Furthermore, L is fluorine, chlorine or bromine.
[0012] Furthermore, the Q is calcium, magnesium, strontium or barium.
[0013] Furthermore, L is fluorine, chlorine or bromine.
[0014] In order to achieve the second purpose, the technical solution adopted by the present invention is:
[0015] A method for preparing a high-nickel positive electrode material co-doped with a rare earth metal, an alkaline earth metal, and a halogen element, for preparing any of the high-nickel positive electrode materials described above, comprising the following steps:
[0016] S100, weighing a lithium source, a high nickel precursor, a rare earth metal salt, an alkaline earth metal salt and a halogen element salt according to the molar ratio of each substance in the molecular formula;
[0017] S200, mixing the substances weighed in S100 uniformly to obtain a first mixture;
[0018] S300, treating the first mixture with a high-temperature solid phase method to obtain a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals, and halogen elements.
[0019] Furthermore, S300 includes:
[0020] S301, calcining the first mixture in the first stage, with the calcination temperature being 400° C. to 600° C. and the sintering time being 4 h to 6 h, to obtain a second mixture;
[0021] S302, calcining the second mixture in a second stage at a calcination temperature of 700° C. to 900° C. for a sintering time of 12 h to 18 h to obtain a third mixture;
[0022] S303, cooling the third mixture to room temperature to obtain a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals, and halogen elements.
[0023] Furthermore, the first calcination and the second calcination process are carried out under the condition of oxygen flow, and the temperature is raised to the calcination temperature at a rate of 2°C / min.
[0024] Furthermore, the symmetrically taken substances in S200 are mixed uniformly by adding alcohol and grinding.
[0025] Furthermore, the molecular formula of the high nickel precursor is as follows: Ni x Co y Mn 1-x-y (OH)2.
[0026] Furthermore, in S100:
[0027] The lithium source is lithium hydroxide monohydrate;
[0028] The rare earth metal salt is lanthanum nitrate, cerium nitrate or yttrium nitrate;
[0029] The alkaline earth metal salt is magnesium carbonate, calcium carbonate, strontium carbonate or barium carbonate;
[0030] The halogen element salt is ammonium fluoride, ammonium chloride, ammonium bromide or ammonium iodide.
[0031] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:
[0032] The present invention adopts the co-doping of rare earth metals, alkaline earth metals and halogen elements. This unique chemical combination forms a new type of composite with a specific electronic structure in the battery material, and these composites play a key role in improving ion conductivity and electronic stability. In particular, the introduction of halogen elements effectively stabilizes the lattice structure of the material, reduces the material decomposition under high voltage, and thus improves the overall performance and thermal stability of the battery. In addition, in addition to the doping effect, the rare earth metals, alkaline earth metals and halogen elements will also synchronously generate a fast ion conductor coating layer, which can effectively control the electrochemical reaction interface of the battery positive electrode material and optimize the diffusion path of lithium ions.
[0033] In the preparation process of positive electrode materials for lithium-ion batteries, especially in the development of high-nickel positive electrode materials, doping technology is an important method to improve the structural stability and electrochemical properties of materials. The introduction of doping elements can be carried out at different stages. The present invention dopes elements on the basis of precursors containing main metal elements. This preparation method allows more refined chemical treatment and subsequent heat treatment to ensure the effective integration and distribution of doping elements. This preparation method can also optimize the chemical state and position of doping elements by heat treatment without affecting the basic lattice structure, thereby improving the electrochemical properties and stability of the material. These advantages not only improve the performance of the material, but also improve the production efficiency and scalability, which meets the needs of industrial production.
[0034] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the SEM image and EDS surface scanning energy spectrum of the high nickel positive electrode material provided in Example 1 of the present invention.
[0036] Figure 2 This is the SEM image and EDS surface scanning energy spectrum of the high nickel positive electrode material provided in Example 2 of the present invention.
[0037] Figure 3 These are the SEM images and EDS surface scanning energy spectrum images of the high nickel positive electrode material provided in Example 3 of the present invention.
[0038] Figure 4 This is the SEM image and EDS surface scanning energy spectrum of the high nickel positive electrode material provided in Example 4 of the present invention.
[0039] Figure 5 1 is the XRD diagram of the high nickel positive electrode material provided in Examples 1 to 4 of the present invention.
[0040] Figure 6 This is a TEM image of the high-nickel positive electrode material provided in Example 2 of the present invention.
[0041] Figure 7 This is a TEM image of the high-nickel positive electrode material provided in Example 4 of the present invention. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the drawings in the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.
[0043] In the following examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are commercially available or prepared by conventional means unless otherwise specified.
[0044] In the following examples:
[0045] The preparation method of the positive electrode sheet is as follows:
[0046] The positive electrode material, conductive agent acetylene black and binder polyvinylidene difluoride (PVDF) were weighed in a mass ratio of 8:1:1 and N-methylpyrrolidone (NMP) solvent was added for grinding and mixing. After forming a uniform slurry, it was coated on the current collector aluminum foil and placed in a vacuum drying oven at 80°C for 12 hours. After drying, the entire electrode sheet was rolled into a circular electrode sheet with a diameter of 12 mm by an electric roller machine for use.
[0047] Assemble the button half-cell and characterize the electrochemistry as follows:
[0048] A lithium manganese battery (CR2025) button half-cell was assembled in an argon glove box, the negative electrode used was a lithium sheet, the separator was a porous polypropylene film (Celgard 2400), and the electrolyte was a mixed solvent of 1 mol / L LiPF6 dissolved in dimethyl carbonate, diethyl carbonate and ethyl carbonate (volume ratio of 1:1:1). The CR2025 button half-cell was used to test the charge and discharge performance of a rare earth metal, alkaline earth metal, and halogen element co-doped high-nickel positive electrode material prepared in the embodiment, and the equipment used was a battery tester (CT 2001A) of Wuhan Blue Electric Electronics Co., Ltd.
[0049] The material structure and morphology characterization methods are as follows:
[0050] Morphology characterization: Scanning electron microscope (SEM) was used, and the equipment used was a field emission scanning electron microscope (FEI Quanta 250). Transmission electron microscope (TEM) was used, and the instrument used was a transmission electron microscope (JEM-2100F) from JEOL, Japan.
[0051] Structural characterization: X-ray diffraction (phase analysis of xray diffraction, referred to as XRD) was used, and the equipment used was UltimaIV-185.
[0052] Example 1
[0053] Preparation of rare earth metal, alkaline earth metal, halogen element co-doped high nickel cathode material Li (Ni 0.8 Co 0.1 Mn 0.1 ) 0.99 La 0.01 Mg 0.01 O 1.98 F 0.02 , the preparation process is as follows:
[0054] Weigh LiOH·H2O, Ni 0.8 Co 0.1 Mn 0.1 (OH)2, La(NO3)3·6H2O, MgCO3 and NH4F are mixed, and alcohol is added to grind evenly to obtain a first mixture; the first mixture is subjected to a first-stage calcination, and the temperature is increased to 400°C at a rate of 2°C / min under oxygen flow conditions, and the calcination temperature is sintered for 6 hours to obtain a second mixture; the second mixture is subjected to a second-stage calcination, and the temperature is increased to 900°C at a rate of 2°C / min under oxygen flow conditions, and the calcination temperature is sintered for 12 hours to obtain a third mixture; the third mixture is naturally cooled to room temperature to obtain a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals and halogen elements.
[0055] The high nickel cathode material prepared in Example 1 was characterized by SEM and EDS. Figure 1As shown. From the SEM image, it can be seen that the secondary particles of the high-nickel material are spherical agglomerates of primary particles, with a particle size of 10μm~12μm, and the primary particle size is about 100nm. The SEM results show that the primary particles of the co-doped sample are refined, and the doping elements do not change the morphology of the high-nickel material. From the Energy Dispersive Spectroscopy (EDS) diagram, it can be seen that La, Mg, and F elements are successfully doped into the high-nickel material and are evenly distributed. Figure 5 The XRD results shown in the figure show that the crystal structure of the prepared materials is a layered structure of the α-NaFeO2 hexagonal system, indicating that the co-doping of anions and cations will not change the main crystal structure inside the material. It should be noted that due to the influence of the high bond energy of La-O, Mg-O and MF, the 003 peak in XRD is also broadened.
[0056] The Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.99 La 0.01 Mg 0.01 O 1.98 F 0.02 The positive electrode materials were assembled into CR2025 button cells for electrochemical performance testing. The cutoff voltage of the activation test at the first 0.1C rate was 2.8V~4.3V (1C=190m A / g), the activation capacity was 215.8 mAh / g, and the coulombic efficiency was 89.1%, indicating that a higher content of F anion doping helps to improve the first week coulombic efficiency. Further cycle performance testing was carried out, and the capacity retention rate was 92.3% after 100 cycles at 1C rate. In the rate performance test, the capacity can still reach 158.6 mAh / g at a high rate of 5C.
[0057] Example 2
[0058] Preparation of rare earth metal, alkaline earth metal, halogen element co-doped high nickel cathode material Li (Ni 0.8 Co 0.1 Mn 0.1 ) 0.98 Ce 0.02 Ca 0.01 O 1.99 F 0.02 , the preparation process is as follows:
[0059] Weigh LiOH·H2O, Ni 0.8 Co 0.1 Mn 0.1 (OH) 2、Ce(NO3)3·6H2O, CaCO3 and NH4F are mixed, and alcohol is added to grind them evenly to obtain a first mixture; the first mixture is subjected to a first-stage calcination, and the temperature is increased to 600°C at a rate of 2°C / min under oxygen flow conditions, and the calcination temperature is sintered for 4 hours to obtain a second mixture; the second mixture is subjected to a second-stage calcination, and the temperature is increased to 700°C at a rate of 2°C / min under oxygen flow conditions, and the calcination temperature is sintered for 18 hours to obtain a third mixture; the third mixture is naturally cooled to room temperature to obtain a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals and halogen elements.
[0060] The high nickel cathode material prepared in Example 2 was characterized by SEM and EDS. Figure 2 As shown in the SEM image, it can be seen that the secondary particles of the high-nickel material are spherical agglomerates of the primary particles, with a particle size of 10μm~12μm, and the primary particle size is about 100nm. The SEM results show that the primary particles of the sample after co-doping are refined, and the doping elements do not change the morphology of the high-nickel material. From the EDS image, it can be seen that the Ce, Ca, and F elements are successfully doped into the high-nickel material and are evenly distributed. Figure 5 The XRD results shown in the figure show that the crystal structure of the prepared materials is a layered structure of the α-NaFeO2 hexagonal system, indicating that the co-doping of anions and cations will not change the main crystal structure inside the material. It should be noted that due to the influence of the high bond energy of Ce-O, Ca-O and MF, the 003 peak in XRD is also broadened. Figure 6 As shown, the introduction of a higher content of rare earth metal ions will generate an oxide coating on the surface without causing damage to the lattice structure.
[0061] The Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.98 Ce 0.02 Ca 0.01 O 1.99 F 0.02The positive electrode materials were assembled into CR2025 button cells for electrochemical performance testing. The cutoff voltage of the activation test at the first 0.1C rate was 2.8V~4.3V (1C=190 mA / g), the activation capacity was 211.4 mAh / g, and the coulombic efficiency was 87.9%. Further cycle performance testing showed that the capacity retention rate was 95.1% after 100 cycles at 1C rate, indicating that high-content rare earth element doping helps to generate a fast ion conductor coating on the surface. This coating helps to alleviate the loss of interface lattice oxygen and can also serve as a physical passivation layer to improve the interface structure, thereby improving the structural stability and having better cycle stability. In the rate performance test, the capacity can still reach 161.3 mAh / g at a high rate of 5C.
[0062] Example 3
[0063] Preparation of rare earth metal, alkaline earth metal, halogen element co-doped high nickel cathode material Li (Ni 0.8 Co 0.1 Mn 0.1 ) 0.98 Ce 0.01 Mg 0.02 O 1.99 Cl 0.01 , the preparation process is as follows:
[0064] Weigh LiOH·H2O, Ni 0.8 Co 0.1 Mn 0.1 (OH)2, Ce(NO3)3·6H2O, MgCO3 and NH4Cl are mixed, and alcohol is added to grind evenly to obtain a first mixture; the first mixture is subjected to a first-stage calcination, and the temperature is increased to 600°C at a rate of 2°C / min under oxygen flow conditions, and the calcination temperature is sintered for 6 hours to obtain a second mixture; the second mixture is subjected to a second-stage calcination, and the temperature is increased to 900°C at a rate of 2°C / min under oxygen flow conditions, and the calcination temperature is sintered for 18 hours to obtain a third mixture; the third mixture is naturally cooled to room temperature to obtain a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals and halogen elements.
[0065] The high nickel cathode material prepared in Example 3 was characterized by SEM and EDS. Figure 3 As shown in the SEM image, it can be seen that the secondary particles of the high-nickel material are spherical agglomerates of the primary particles, with a particle size of 10μm~12μm, and the primary particle size is about 100nm. The SEM results show that the primary particles of the sample after co-doping are refined, and the doping elements do not change the morphology of the high-nickel material. From the EDS image, it can be seen that Ce, Mg, and Cl elements are successfully doped into the high-nickel material and are evenly distributed. Figure 5The XRD results shown in the figure show that the crystal structure of the prepared materials is a layered structure of the α-NaFeO2 hexagonal system, indicating that the co-doping of anions and cations will not change the main crystal structure inside the material. It should be noted that due to the influence of the high bond energy of Ce-O, Mg-O and M-Cl, the 003 peak in XRD is also broadened.
[0066] The Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.98 Ce 0.01 Mg 0.02 O 1.99 Cl 0.01 The positive electrode materials were assembled into CR2025 button batteries for electrochemical performance testing. The cutoff voltage of the first activation test at a rate of 0.1C was 2.8V~4.3V (1C=190 mA / g), the activation capacity was 208.9 mAh / g, and the coulombic efficiency was 87.4%. Further cycle performance tests were carried out, and the capacity retention rate was 93.6% after 100 cycles at a rate of 1C. In the rate performance test, the capacity can still reach 168.4 mAh / g at a high rate of 5C. High-content alkaline earth metal ion doping can increase the interlayer spacing of the Li layer while inhibiting the increase in the degree of lithium-nickel mixing in the material, thereby reducing the resistance of lithium ions to deintercalation in high-nickel layered oxide materials and improving the rate performance of the material.
[0067] Example 4
[0068] Preparation of rare earth metal, alkaline earth metal, halogen element co-doped high nickel cathode material Li (Ni 0.8 Co 0.1 Mn 0.1 ) 0.98 Y 0.02 Sr 0.01 O 1.99 Cl 0.02 , the preparation process is as follows:
[0069] Weigh LiOH·H2O, Ni 0.8 Co 0.1 Mn 0.1(OH)2, Y(NO3)3·6H2O, CaCO3 and NH4F are mixed, and alcohol is added to grind evenly to obtain a first mixture; the first mixture is subjected to a first-stage calcination, and the temperature is increased to 500°C at a rate of 2°C / min under oxygen flow conditions, and the calcination temperature is sintered for 6 hours to obtain a second mixture; the second mixture is subjected to a second-stage calcination, and the temperature is increased to 900°C at a rate of 2°C / min under oxygen flow conditions, and the calcination temperature is sintered for 18 hours to obtain a third mixture; the third mixture is naturally cooled to room temperature to obtain a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals and halogen elements.
[0070] The high nickel cathode material prepared in Example 4 was characterized by SEM and EDS. Figure 4 As shown in the SEM image, it can be seen that the secondary particles of the high-nickel material are spherical agglomerates of the primary particles, with a particle size of 10μm~12μm, and the primary particle size is about 100nm. The SEM results show that the primary particles of the sample after co-doping are refined, and the doping elements do not change the morphology of the high-nickel material. From the EDS image, it can be seen that the Y, Sr, and Cl elements are successfully doped into the high-nickel material and are evenly distributed. Figure 5 The XRD results shown in the figure show that the crystal structure of the prepared materials is a layered structure of the α-NaFeO2 hexagonal system, indicating that the co-doping of anions and cations will not change the main crystal structure inside the material. It should be noted that due to the influence of the high bond energy of YO, Sr-O and M-Cl, the 003 peak in XRD is also broadened. Figure 7 As shown in the figure, the introduction of a high content of rare earth metal ions will generate a coating layer on the surface without causing damage to the lattice structure. Through HRTEM analysis of the surface coating layer component structure, it can be seen that the generated coating layer is a Li3YCl6 fast ion conductor coating layer. This coating layer establishes a three-dimensional network structure with high conductivity between the particles, which significantly improves the Li + conduction rate, further improving rate performance.
[0071] The Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.98 Y 0.02 Sr 0.01 O 1.99 Cl 0.02The positive electrode materials were assembled into CR2025 button cells for electrochemical performance testing. The cutoff voltage of the first activation test at a rate of 0.1C was 2.8V~4.3V (1C=190 mA / g), the activation capacity was 214.5 mAh / g, and the coulombic efficiency was 88.6%. Further cycle performance testing showed that the capacity retention rate was 94.8% after 100 cycles at a rate of 1C, indicating that a high content of rare earth elements doping helps to generate a fast ion conductor coating on the surface. The Li3YCl6 coating helps to alleviate the loss of interface lattice oxygen and can also serve as a physical passivation layer to improve the interface structure, thereby improving the structural stability and having better cycle stability. In the rate performance test, the capacity can still reach 165.7 mAh / g at a high rate of 5C.
[0072] Comparative Example 1
[0073] Preparation of high nickel cathode material for LiNi 0.8 Co 0.1 Mn 0.1 O2, the preparation process is as follows:
[0074] Weigh LiOH·H2O, Ni in the corresponding molar ratio in the molecular formula 0.8 Co 0.1 Mn 0.1 (OH)2, and then mixed, and then ground evenly after adding alcohol. The calcination conditions are the same as those in Example 2 to obtain a high-nickel positive electrode material, LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0075] The LiNi prepared in Comparative Example 1 0.8 Co 0.1 Mn 0.1 The O2 positive electrode material was assembled into a CR2025 button cell for electrochemical performance testing. The cutoff voltage of the activation test at the first 0.1C rate was 2.8V~4.3V (1C=190 mA / g), the activation capacity was 198.5 mAh / g, and the coulombic efficiency was 85.3%. Further cycle performance testing was carried out, and the capacity retention rate was 90.4% after 100 cycles at a 1C rate. In the rate performance test, the capacity was 150.2 mAh g-1 at a high rate of 5C. The relevant electrical properties are lower than those of the high-nickel positive electrode material prepared in Example 2, indicating that the embodiments of the present invention help to utilize the advantages of anion and cation doping and synergistically modify the positive electrode material to achieve the best effect.
[0076] Comparative Example 2
[0077] Preparation of rare earth metal, alkaline earth metal, halogen element co-doped high nickel cathode material Li (Ni 0.8 Co 0.1 Mn0.1 ) 0.96 Ce 0.03 Ca 0.03 O 1.97 F 0.03 , the preparation process is as follows:
[0078] Weigh LiOH·H2O, Ni 0.8 Co 0.1 Mn 0.1 (OH)2, Ce(NO3)3·6H2O, CaCO3 and NH4F were mixed, and then ground evenly after adding alcohol. The calcination conditions were the same as those in Example 2 to obtain a high-nickel positive electrode material:
[0079] Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.96 Ce 0.03 Ca 0.03 O 1.97 F 0.03 .
[0080] The Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.96 Ce 0.03 Ca 0.03 O 1.97 F 0.03 . The positive electrode materials were assembled into CR2025 button batteries for electrochemical performance testing. The cutoff voltage of the first activation test at a rate of 0.1C was 2.8V~4.3V (1C=190 mA / g), the activation capacity was 180.9 mAh / g, and the coulombic efficiency was 82.6%. Further cycle performance tests were carried out, and the capacity retention rate was 82.7% after 100 cycles at a rate of 1C. In the rate performance test, the capacity was 142.1 mAh / g at a high rate of 5C. The relevant electrical properties are all lower than those of the high-nickel positive electrode material prepared in Example 2, indicating that doping with higher contents of rare earth metals, alkaline earth metals, and halogen elements cannot enhance the modification effect of each other, and the proportion of the content of each component needs to be carefully controlled.
[0081] Table 1 is a comparison of the electrochemical performance of batteries assembled with high nickel positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 and 2.
[0082] Table 1
[0083]
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element, characterized in that: The molecular formula of the high nickel positive electrode material is as follows: ; Wherein, P is a rare earth metal, Q is an alkaline earth metal, and L is a halogen element; Among them, x ≥ 0.6, 0.01 ≤ a ≤ 0.02, 0.01 ≤ b ≤ 0.02, 0.01 ≤ c ≤ 0.02; The method for preparing the high-nickel positive electrode material comprises the following steps: S100, weighing a lithium source, a high nickel precursor, a rare earth metal salt, an alkaline earth metal salt and a halogen element salt according to the molar ratio of each substance in the molecular formula; S200, mixing the substances weighed in S100 uniformly to obtain a first mixture; S300, treating the first mixture with a high-temperature solid phase method to obtain a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals, and halogen elements.
2. A high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element as claimed in claim 1, characterized in that: The P is lanthanum, cerium or yttrium.
3. The high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element as claimed in claim 1, characterized in that: The Q is calcium, magnesium, strontium or barium.
4. The high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element as claimed in claim 1, characterized in that: The L is fluorine, chlorine or bromine.
5. The high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element as claimed in claim 4, characterized in that: S300 includes: S301, calcining the first mixture in the first stage, with the calcination temperature being 400° C. to 600° C. and the sintering time being 4 h to 6 h, to obtain a second mixture; S302, calcining the second mixture in a second stage at a calcination temperature of 700° C. to 900° C. for a sintering time of 12 h to 18 h to obtain a third mixture; S303, cooling the third mixture to room temperature to obtain a high-nickel positive electrode material co-doped with rare earth metals, alkaline earth metals, and halogen elements.
6. The high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element as claimed in claim 1, characterized in that: The first and second calcination processes are carried out under the condition of oxygen flow, and the temperature is raised to the calcination temperature at a rate of 2°C / min.
7. The high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element as claimed in claim 1, characterized in that: In S200, the symmetrically taken substances are mixed uniformly by adding alcohol and grinding.
8. The high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element as claimed in claim 1, characterized in that: The high nickel precursor is Ni x Co y Mn 1-x-y (OH)2, x≥0.
6.
9. The high nickel positive electrode material co-doped with rare earth metal, alkaline earth metal and halogen element as claimed in claim 1, characterized in that: In S100: The lithium source is lithium hydroxide monohydrate; The rare earth metal salt is lanthanum nitrate, cerium nitrate or yttrium nitrate; The alkaline earth metal salt is magnesium carbonate, calcium carbonate, strontium carbonate or barium carbonate; The halogen element salts are ammonium fluoride, ammonium chloride and ammonium bromide.
Citation Information
Patent Citations
Cathode material for lithium ion battery and preparation method thereof, cathode and lithium ion battery
CN109244365A
Sc-doped modified high-nickel ternary cathode material
CN109950534A